MODERN DIRECTION FOR IMPROVING THE QUALITY OF TRAINING STUDENTS OF DENTAL FACULTY - M.V. Storozheva; S.N. Grigorov; L.P. Rekova (Ukrainian Medical Stomatological Academy, 2015)
In various studies of the structure of human activities, including professional ones, the main thing in this context is given to its components, as the motive and purpose. These components affect the personal and professional development of medical students and medical interns. Readiness for continuous improvement of professional knowledge and skills positively affects the attitude to the chosen specialty. The search for methods of motivation for the retention and use of knowledge, practical skills in students is an important task in teaching one of the most interesting and at the same time the most difficult dental disciplines as "Dental Surgery". In the formation of students' positive attitude to learning activities, acquiring new knowledge and skills is of primary importance. Learning goals and interests of students at training is a necessary component in the organization of lectures and practical exercises, motivation to succeed professionally. For the formation of motives of a successful teacher, it is necessary to organize and implement the entire arsenal of training activities: verbal, visual and practical, reproductive and exploratory, deductive and inductive methods. In addition, each of methods of organization of training activities at the same time has not only informative, instructional, but also motivational function. Group methods of stimulation and motivation can be divided into two subgroups. The first of these are the methods of formation of informative interest in students. Research on the issue of formation of informative interest displays that it is characterized by three mandatory factors: positive emotion in relation to the activities, the presence of cognitive side of emotions, the presence of the direct motive, coming from the activity itself. The second are the methods, mainly aimed at creating the sense of duty and responsibility in learning. Moreover, in the pedagogical process there is an important factor of raising positive emotions in relation to educational activity, its forms and methods of implementation. One of the methods included in the training methods of emotional stimulation is called the reception of creating the entertaining situations in class - the introduction to the learning process of practical examples of the use in the treatment of patients with specific characteristics (from personal medical experience). In order to stimulate interest in learning, it is also possible to use the method of cognitive games based on the establishment of the learning process of game situations. One way to encourage and motivate to study is method of creating a situation of cognitive dispute. At the same time, students are divided into supporters and opponents of a clinical case that directly stimulates the maximum specification of knowledge. The most striking example of this method is to discuss the indications and contraindications for tooth extraction, which allows supporters of the "right" position to objectively prove their position. In the course of solving situations, students learn to act in the "team", to analyze the educational situation and choose the best option in the context of the problem. These innovative approaches develop flexibility and originality of thinking; promote highly motivated training, development of students' abilities. From the pedagogical point of view, there is an increase of ratings of individual students and the entire group. All this is necessary for the implementation of the new Law of Ukraine "On Higher Education" and the growing need in training specialists.